Between French and English, Between Ethnography and Assimilation: Strategies for Translating Moncton’s Acadian Vernacular - Leclerc, Catherine (TTR)

(untitled) (Association canadienne de traductologie, 2005)
Chiac, the hybrid vernacular spoken by Acadians in the Moncton region, is increasingly used in works of fiction. By placing it on a par with French, Acadian novelists attempt to legitimize it as the language of a modern and urban Acadie. Their task is a difficult one, to which they respond with ambivalence: Chiac inscribes a difference which marginalizes them, whereas its absence amounts to a disappearance into the French norm. As a consequence, writers using Chiac face the challenge of making room for hybridity without dissociating themselves from their francophone identity. In their encounter with Chiac, translators of Acadian literature into English face a challenge of their own. Both multilingualism and vernacular languages have been deemed untranslatable, and Chiac happens to be at once multilingual and a vernacular. The dilemma faced by these translators is hence not too far from the dilemma of writers of Chiac: how much difference should they erase, how much should they insist on it at the risk of confirming stereotypes? How can they assist and pursue attempts at legitimization? How can they avoid assimilation into English on the one hand, and ethnography on the other? This article investigates the strategies brought into play by two translators who have tackled Chiac and its ambivalent use by Acadian novelists: Robert Majzels, translator of France Daigle, and Jo-Anne Elder, translator of Gérald Leblanc.Keywords: Chiac, Acadian literature, Acadian literature in translation, literary multilingualism, sociolects and vernaculars.